2018
DOI: 10.1007/s40572-018-0190-3
|View full text |Cite
|
Sign up to set email alerts
|

Health Implications of Climate Change: a Review of the Literature About the Perception of the Public and Health Professionals

Abstract: Purpose of ReviewThrough a systematic search of English language peer-reviewed studies, we assess how health professionals and the public, worldwide, perceive the health implications of climate change.Recent FindingsAmong health professionals, perception that climate change is harming health appears to be high, although self-assessed knowledge is low, and perceived need to learn more is high. Among the public, few North Americans can list any health impacts of climate change, or who is at risk, but appear to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 66 publications
(77 reference statements)
8
85
0
Order By: Relevance
“…Comprehensive literature reviews have been recently performed to assess the current state of the science regarding climate change 2,8 , associated adverse health outcomes from weather-related disasters 15,16,38,39,66,67 , public health disaster research 68,69 , and disaster epidemiology 70 . However, we are unaware of any systematic literature review of the intersections between climate change, adverse weather-related disasters, and population health adaptation strategies.…”
Section: Methodsmentioning
confidence: 99%
“…Comprehensive literature reviews have been recently performed to assess the current state of the science regarding climate change 2,8 , associated adverse health outcomes from weather-related disasters 15,16,38,39,66,67 , public health disaster research 68,69 , and disaster epidemiology 70 . However, we are unaware of any systematic literature review of the intersections between climate change, adverse weather-related disasters, and population health adaptation strategies.…”
Section: Methodsmentioning
confidence: 99%
“…To be clear, bioinformation has a central role in TER as well because it informs the allostasiome, which is essential for patient-centered care and individual patient data research and analysis [ 9 , 10 ]. Bioinformation plays an essential role in the concerted global action to address and control the complex and multi-dimensional medical emergency resulting from the climate change crisis [ 11 , 12 ].…”
Section: Bioinformation For Termentioning
confidence: 99%
“…While research on public awareness and perceptions of climate change health impacts has been undertaken around the world (e.g. [12,[22][23][24][25] ), research in Canada is limited to date. In a review of the literature that does exist, Hathaway and Maibach found that relatively few North Americans associate climate change with health harms [24].…”
Section: Introductionmentioning
confidence: 99%
“…[12,[22][23][24][25] ), research in Canada is limited to date. In a review of the literature that does exist, Hathaway and Maibach found that relatively few North Americans associate climate change with health harms [24]. Other studies have similarly found that when prompted, Canadians can name some health impacts of climate change, but the overall link between health and climate change lacks salience for the public [26,27].…”
Section: Introductionmentioning
confidence: 99%